2021
DOI: 10.1002/hbm.25678
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry tracks cognitive load and salience network activity in a working memory functional magnetic resonance imaging task

Abstract: The diameter of the human pupil tracks working memory processing and is associated with activity in the frontoparietal network. At the same time, recent neuroimaging research has linked human pupil fluctuations to activity in the salience network. In this combined functional magnetic resonance imaging (fMRI)/pupillometry study, we recorded the pupil size of healthy human participants while they performed a blockwise organized working memory task (N‐back) inside an MRI scanner in order to monitor the pupil fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…2e; Supplementary Table. 1), consistent with previous studies 14,16,22 . At the time point with their highest correlation with BMBU's decision uncertainty (Supplementary Fig.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…2e; Supplementary Table. 1), consistent with previous studies 14,16,22 . At the time point with their highest correlation with BMBU's decision uncertainty (Supplementary Fig.…”
supporting
confidence: 93%
“…'The pre-congruence effect is straightforward but has not been established empirically. The neglect of this obvious source of the variability in decision variability is odd, given the fundamental roles of decision uncertainty in adaptive human behavior such as volatility monitoring 11 , learning from errors 12 , and executive control 13 , and its wide-ranging associations with behavioral (response time [14][15][16][17] ), physiological (pupil-size 14,15 ), and neural (salience network 11,[14][15][16]18 ) measures. Here, we probed human response time (RT), pupil size, and neural activity to ascertain the presence of the pre-congruence effect and assess its contribution to the variability in decision uncertainty.We recruited 41 human participants and asked them to perform a binary classification task.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It scales with task difficulty and with motivation and task engagement (Hopstaken et al, 2015; Massar et al, 2016, 2019; Schneider et al, 2018). Pupillometry studies involving the N‐Back task similarly found increased pupil diameter with higher working memory load, and with reward motivation (Mies et al, 2018; Peysakhovich et al, 2017; Yeung et al, 2021), related to activation of effort‐related brain circuitry, including dorsal anterior cingulate cortex, and anterior insula (Fietz et al, 2022).…”
Section: Discussionmentioning
confidence: 99%